A Previously Unidentified Tuff in the Archaic Temple Podium at Sant'Omobono, Rome and its Broader Implications - Brocato, Paolo; Diffendale, Daniel P.; Di Giuliomaria, Desirè; Gaeta, Mario; Marra, Fabrizio; Terrenato, Nicola (Journal of Mediterranean Archaeology, 2019)
This study reports on the discovery that the podium of the archaic temple in the Forum Boarium of Rome was built with a previously unknown tuff, of non-local origin. On the basis of detailed comparative petrographic and geochemical tests, it has been established that the blocks employed to build the earliest temple so far discovered in Rome belonged to a distinctive facies of tufo lionato that had never been characterized before, in contrast to what was reported by previous excavators. The blocks must have come from a quarry in the Anio River Valley, several kilometers from the construction site, making the Sant'Omobono temple the earliest known Roman building that extensively employed imported materials. The metrology of the blocks is also unique. This particular volcanic stone was probably chosen for its much greater resistance to weathering compared to the local tuffs, a trait that was essential in the flood-prone location, not far from the Tiber riverbank, where the temple was situated. The labor-intensive sourcing may also explain the dainty size of the temple podium in comparison to other sixth-century bc temples in the region. The choice made by the builders indicates far greater sophistication and technical awareness than they have generally been credited with. The new discovery is placed in the context of the quickly accumulating archaeological record of sixth-century bc Rome, which suggests a dramatic increase in the number and scale of monumental projects in the expanding city.